(untitled) (Journal of Nuclear Technology in Applied Science, 2022)
Reliable information on soil loss is essential to establish the effectiveness of soil management practices. The present work aims at assessing short-term soil erosion and evaluating the efficiency of some agricultural practices, through the use of Beryllium-7 fallout technique. Sehoul catchment is located 40 km far from Rabat, between Maamora forest in the north and Grou River in the south. This region is subjected to significant soil degradation due to intense rainfall. The area suffers from mismanaged practices which deteriorate existent agricultural lands. The existent agricultural practices are Monoculture (MC), Cereal/Cereal Rotation (CCR) and Legume/ Cereal Rotation (LCR). Three representative fields including Vineyard as MC, Barley/Wheat as CCR and Bean/Wheat as (LCR), were investigated in 2009 and 2010. In 2009, results showed that the estimated net erosion rates were -6.7, -5.8, and 0.9 t ha-1 for CCR, LCR and MC, respectively, at a rainfall amount of 664 mm showing that MC is the best conservation practice followed by LCR then CCR. In 2010, the rainfall amount increased to 929 mm and the estimated net erosion rates were -13.9, 1.7, and -3.3 t ha-1 for CCR, LCR, and MC respectively, showing a decrease in soil loss in LCR despite heavy rainfall and emphasis that LCR is the best-recommended conservation practice followed by MC then CCR. Comparing the average net erosion rate for different agricultural practices for the two years, we can conclude that LCR is the most efficient conservation practice, particularly under heavy rainfall.